On Stochastic Entry and Exit without Expectations - Inaba, F. S. (Review of Economic Studies, 1978)
Journal Article On Stochastic Entry and Exit without Expectations Get access Frederick S. Inaba Frederick S. Inaba Washington State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 535–545, https://doi.org/10.2307/2297255 Published: 01 October 1978 Article history Received: 01 February 1976 Accepted: 01 July 1977 Published: 01 October 1978